Individual host factors and co-infections affect the probability and excretion intensity of endoparasite infections in dairy cows - Anna Sophie Hecker; Marie-Kristin Raulf; Sven König; Katharina May; Christina Strube (Parasites & Vectors)
Abstract Background Endoparasite infections cause economic losses in dairy farming. Understanding the factors that influence endoparasite prevalence and egg/oocyst excretion is essential for effective parasite control. Environmental and management factors play an important role at herd level; however, factors related to the individual cow, such as the parity number or lactation stage, also contribute to infection. In addition, it is still unclear to what extent co-infections with other endoparasites influence prevalence and egg/oocyst excretion rates. Methods Faecal samples from 1,126 cows from 24 dairy herds were copromicroscopically examined for endoparasite infections. Hurdle models were applied to test the effect of parity number, lactation stage and co-infections on the probability and intensity of egg/oocyst excretion of strongyles, Fasciola hepatica, rumen flukes and coccidia. Results Strongyle eggs were present in all herds and 45.9% of individual cows, F. hepatica eggs in 75.0% of herds and 9.9% of cows, rumen fluke eggs in 62.5% of herds and 26.5% of cows and coccidian oocysts in 91.7% of herds and 18.7% of cows. Eggs of Moniezia spp., Trichuris spp. and Capillaria spp. were detected sporadically. Model analysis revealed that the probability of strongyle egg excretion decreased after the first parity, presumably as a result of developing immunity, yet an increase was observed after the fourth parity. With increasing parity number, excretion probability of F. hepatica and excretion intensity of rumen flukes increased. Coccidian oocysts excretion was highest in first-parity cows. The lactation stage affected strongyle egg excretion, with the highest probability in early lactation, possibly linked to the negative energy balance in this period. Strongyle co-infections increased the probability of coccidian oocyst excretion (P = 0.008), and coccidian co-infections increased both the probability (P = 0.011) and intensity (P = 0.007) of strongyle egg excretion. Furthermore, coccidian co-infections were associated with a decreased excretion intensity of rumen fluke eggs (P = 0.022). Conclusions The identification of age groups that are more susceptible to or more likely to spread certain endoparasite taxa and the synergism between strongyle egg and coccidian oocyst excretion can help to implement effective targeted monitoring and control strategies to optimise parasite management in dairy herds. Graphical Abstract